Digital literacy games: a systematic literature review - De La Hera, Teresa; Sanz, Laura Cañete; Sierra, Nuria Navarro; Jansz, Jeroen; Kneer, Julia; Glas, René; van Vught, Jasper (Frontiers in Communication, 2024)
This paper presents the results of a systematic literature review of academic publications about digital literacy games. We have analyzed a total of 30 papers and book chapters published in English, Spanish, Portuguese and Dutch between 2005 and 2021 and stored in Scopus. The results of this literature review report on: (1) the topics of the games discussed in the publications; (2) the digital literacy competencies supported by the games studied in the publications; (3) the effects of these games; and (4) ten game design considerations for digital literacy games collected from the results of the publications. This paper also provides detailed access to the original sources by reporting on which paper addressed what.